The Role of Self-Organized TiO2 Nanotube Thickness on the Electrochemical Performance of Anodes for Li-Ion Microbatteriess - Ghigo, Clement; Sopha, Hanna Ingrid; Sepulveda Sepulveda, Lina Marcela; Hromádko, Luděk; Rodriguez Pereira, Jhonatan; Vacandio, Florence; Denoue, Killian; Macák, Jan; Djenizian, Thierry (Wiley-VCH, 2024)
Self-organized TiO2 nanotube (TNT) layers with different thicknesses are prepared by anodization of Ti foils and then characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), and electrochemical techniques to be used as potential anodes for Li-ion microbatteries. Electrochemical behaviors between 1 and 190 mu m thick electrodes, which are the thickest ever studied layers as electrode, have been evaluated by cyclic voltammetry (CV) and chronopotentiometry at various kinetics. The highest areal capacity is obtained for TNT layers of 190 mu m providing an initial discharge capacity of approximate to 5.3 mAh cm(-2) at C/10. At faster kinetics, the approximate to 80 mu m thick TNT layer reveals the best electrochemical behavior by offering 256 mu Ah cm(-2) at 5 C and a good stability for 200 cycles at C/5. The influence of the increasing thickness on the electrochemical performance at fast rates can be attributed to the uncomplete reaction of TNT layers with Li ions and the enhancement of the formation of a solid electrolyte interphase. It is also shown that a very thick electrode is not able to sustain long and very fast cycles due to the mechanical deformations occurring during the successive insertion/extraction of Li ions.
Role tloušťky vrstev samoorganizovaných TiO2 nanotrubic na elektrochemický výkon anod pro Li-Ion mikrobaterie
Keywords: anodes; energy storage; Li-ion microbatteries; TiO2 nanotubes; Anody; skladování energie; Li-ion mikrobaterie; TiO2 nanotrubice